Loss of Cellular Inhibitor of Apoptosis Protein 2 Reduces Atherosclerosis in Atherogenic apoE−/− C57BL/6 Mice on High‐Fat Diet. Issue 5 (26th September 2013) - Sleiman, Lyne; Beanlands, Rob; Hasu, Mirela; Thabet, Mohamed; Norgaard, Alex; Chen, YX; Holcik, Martin; Whitman, Stewart
Abstract : Background: Cellular inhibitor of apoptosis protein 2 (cIAP2) is predicted to participate in atherosclerosis; however, its direct role in atherosclerosis development has not been investigated. We aimed to examine and assess the loss of cIAP2 on atherosclerosis lesion development. Methods and Results: We used apoE −/− C57BL/6 male mice, either cIAP2 −/− or cIAP2 +/+ . At 8 weeks, mice were fed a high‐fat diet (HFD) for 4 and 12 weeks. Aortic root was serially sectioned and stained with Sudan IV, CD68, α‐actin, and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL). cIAP2 −/− mice displayed a significant decrease in atherosclerotic lesion's macrophage number after 4 weeks of HFD. Similarly, decrease in lesion area at 4 and 12 weeks HFD was detected by use of en face analysis ( cIAP2 −/− 0.58±0.37% versus cIAP2 +/+ 1.51±0.79% [ P =0.0056]); ( cIAP2 −/− 9.34±4.88% versus cIAP2 +/+ 17.65±6.24% [ P =0.0019]). Aortic root lesion area after 4 and 12 weeks of HFD also decreased ( cIAP2 −/− 0.0328±0.014 mm 2 versus cIAP2 +/+ 0.0515±0.021 mm 2 [ P =0.022]); ( cIAP2 −/− 0.3614±0.1157 mm 2 versus cIAP2 +/+ 0.4901±0.125 mm 2 [ P =0.065]). TUNEL analysis after 4 and 12 weeks of HFD showed a 2.5‐fold increase in TUNEL+ cells ( cIAP2 −/− 4.47±2.26% versus cIAP2 +/+ 1.74±0.98% [ P =0.036]); ( cIAP2 −/− 2.39±0.75% versus cIAP2 +/+ 1.29±0.47% [ P =0.032]). Smooth muscle cell content in cIAP2 −/− mice was 3.075±3.3% compared with cIAP2 +/+ with 0.085±0.1% ( P =0.0071). Conclusions: Results uncover a key role for cIAP2 in atherosclerotic lesion development, and targeting it may represent a novel therapeutic strategy.